Perubahan aktivitas promosi perpustakaan kantor perwakilan Bank Indonesia Jawa Tengah di masa Pembatasan Sosial Berskala Besar (PSBB) - Patricia Ikaria Ratnasari; Muhammad Sulhan (FPPTI Jawa Tengah, 2023)
Promotion is essential for the Central Java Bank Indonesia Representative Office Library is in a state of the COVID-19 pandemic. Upgrades need to be adjusted to changing user behavior and needs. Restricting access presents challenges, but libraries try to maximize promotion in a limited environment. This research analyzed the differences in promotional activities before and during PSBB to understand their impact on library existence and services. This study used a qualitative approach to understand Central Java Bank Indonesia Representative Office Library promotion activities changes during the PSBB. Selection of informants using purposive sampling with two librarians as informants. Data was collected through in-depth interviews, document analysis, and observation. Central Java Bank Indonesia Representative Office Library promotion activities changes during the PSBB was significant, namely switching from physical promotions to online, focusing on digital collections, and promoting virtual events for visitors. Promotional messages emphasize the benefits of online services, free access to digital collections, and involvement during PSBB. This change allows for adjustments to the promotion mix and optimization of the service in the future. Central Java Bank Indonesia Representative Office Library needs to evaluate promotional activities during the PSBB, understand changes in user behavior, and work closely with the mass media. Flexibility and adaptation are vital in dealing with future changes. Regular promotion strategy adjustments are essential to stay relevant and connected with users.